Mobile banking and inclusive innovation at the bottom of the pyramid in South Africa - Maseko, Matshidiso (My University, 2022)
Financial institutions and technology have a critical role to play in alleviating the plight of people leaving in poverty through innovative and inclusive offerings. Pro-poor innovation is mostly done through non-profit charity organizations. It is now increasingly recognized that inclusive innovations of people living at the bottom of the pyramid (BOP) can be developed and diffused through appropriate and relevant market mechanism. The aim of this study is to examine, through a quantitative analysis, the benefits, and challenges of mobile banking innovations development for BOPs in South Africa. A questionnaire was administered on participants, randomly selected, in Gauteng province. Effective mobile banking implementation is possible with clear regulations on pricing, competition, prudential banking, deposits, and payment system regulation to ensure transparency, consumer protection, safety, integrity, secure and efficient systems. With partnerships, co-creation and collaborative efforts can be combined to bring more awareness to mobile banking innovations. With partnerships, co-creation and collaborative efforts can be combined to bring more awareness to mobile banking innovations. It is recommended that a competitive mobile banking environment, key stakeholder partnerships, adequate awareness campaigns, infrastructure development, BOP clientele focus and balanced regulatory policies be created to facilitate growth within the mobile banking innovation of BOPs in South Africa.
A research report submitted to the Faculty of Commerce, Law and Management, Wits Business School in the University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Innovation Studies.
Keywords: Inclusive innovation; Bottom of the pyramid; Mobile banking; SDG-8: Decent work and economic growth